2019
DOI: 10.1111/ssqu.12586
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Globalization on Women's and Non‐Women's Protest*

Abstract: Objectives We advance hypotheses on the extent to which the three main aspects of globalization—economic, political, and social—fuel mass protest and delineate how these effects can be especially instrumental in understanding collective mass mobilization among a historically disadvantaged group, women. Methods We use new and updated data on anti‐government protest to examine the covariates of protest intensity cross‐nationally over time. Results Results from the data analysis indicate that while political glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…We compute the proportion of women's protests using countrylevel panel data on women's protests and total protests from Bell et al (2019) the 27/10/2020. When generating ratios of women to male outcomes these are Winsorized at the 1 st and 99 th percentiles to avoid outliers in cases where the denominator is very small.…”
Section: Online Appendix Tablesmentioning
confidence: 99%
“…We compute the proportion of women's protests using countrylevel panel data on women's protests and total protests from Bell et al (2019) the 27/10/2020. When generating ratios of women to male outcomes these are Winsorized at the 1 st and 99 th percentiles to avoid outliers in cases where the denominator is very small.…”
Section: Online Appendix Tablesmentioning
confidence: 99%
“…Most studies focus on women's participation in North America and Western Europe only (Costain 1992; Soule et al 1999). The studies that do exist, however, often find very similar patterns of women's participation in protest to that of protest that does not center on women's issues, especially when compared with other historically disadvantaged groups (Murdie and Peksen 2015; Bell et al 2019).…”
Section: Where Are All the (Female) Activists?mentioning
confidence: 99%
“…Repression and injustice can mobilize individuals to take to the streets. Research on women's protest has similarly found that a lack of respect for women's rights often accompanies mobilization (Bell, Murdie, and Peksen 2019; Costain 1992; Murdie and Peksen 2015).…”
Section: Where Are All the (Female) Activists?mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we find much auxiliary evidence concerning the indirect mechanism or middle step in our theoretical logic. Abortion rights restrictions limit citizen trust in government (Haerpfer et al 2021) and reduce non-violent protest (Bell, Murdie, and Peksen 2019) (Williams and Whitten 2012). Panel A shows that a country with the median respect for abortion rights (a score of 4 on the CAI #1 measure) is expected to increase their respect for social group equality in civil liberties over time while countries with lower respect of abortion rights are either supposed to stay relatively constant (the score of 3 on the CAI #1 measure) or diminish their respect for social group equality over time.…”
Section: Exploring the Causal Process And Extensionsmentioning
confidence: 99%